Association between the Organizational Culture and Burnout among the Faculty Members of Medical Institutions and Teaching Hospitals of Punjab Pakistan - Rabia Malik, Qundeel Zahra, Fatima Aslam, Rehan Ahmed Khan, Usman Mahboob, Remsha Mustafa, Waqas Latif (Pakistan Journal of Medical & Health Sciences, 2022)
It has been empirically suggested that organizational culture and burnout are strongly interlinked. Aims: To assess the association between organizational culture and burnout among faculty members of medical colleges and their affiliated hospitals of Punjab, Pakistan. Study Design: Cross-sectional study. Methodology: Present study enrolled 444 participants who full-filled inclusion criteria. Informed written consent was taken from all the participants. They completed Hofstede Organizational Culture Questionnaire and Maslach Burnout Inventory respectively. Statistical analysis: Pearson Product Moment Correlation Analysis was applied with P-value of < 0.05 taken as significant. Results: The results showed that the participants perceived parochial organizational culture in medical colleges and affiliated hospitals of Punjab. The findings of Pearson Product Moment Correlation showed significant relationship between these two factors among employees. Conclusion: It was concluded that a favourable working environment is necessary to reduce the incidence of job burnout in every set-up especially the higher education sector. Academicians suffering from burnout must be identified and adequately managed.